2015
DOI: 10.1016/j.antiviral.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Broad-range inhibition of enterovirus replication by OSW-1, a natural compound targeting OSBP

Abstract: Enteroviruses, e.g., polio-, coxsackie-and rhinoviruses, constitute a large genus within the Picornaviridae family of positive-strand RNA viruses and include many important pathogens linked to a variety of acute and chronic diseases. Despite their huge medical and economic impact, no approved antiviral therapy is yet available. Recently, the oxysterol-binding protein (OSBP) was implicated as a host factor for enterovirus replication. Here, we investigated the antiviral activity of the natural compound OSW-1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 16 publications
1
52
0
5
Order By: Relevance
“…Similar to the physiological role of OSBP, enteroviruses exploit the PI4KIIIb-PI4P-OSBP pathway to import cholesterol into their ROs [59][60][61]. Pharmacological inhibition of this pathway by targeting either PI4P production or OSBP-mediated lipid shuttling efficiently impaired enterovirus replication [23,36,[59][60][61][62][63][64]. The observation that replication is hampered when PI4P transported to the ER is not hydrolyzed upon knockdown of Sac1 [23,60] underscores the importance of the cholesterol/PI4P-counterflux for enterovirus replication.…”
Section: Pi4p-dependent Cholesterol Recruitment To Ros Via Mcssmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar to the physiological role of OSBP, enteroviruses exploit the PI4KIIIb-PI4P-OSBP pathway to import cholesterol into their ROs [59][60][61]. Pharmacological inhibition of this pathway by targeting either PI4P production or OSBP-mediated lipid shuttling efficiently impaired enterovirus replication [23,36,[59][60][61][62][63][64]. The observation that replication is hampered when PI4P transported to the ER is not hydrolyzed upon knockdown of Sac1 [23,60] underscores the importance of the cholesterol/PI4P-counterflux for enterovirus replication.…”
Section: Pi4p-dependent Cholesterol Recruitment To Ros Via Mcssmentioning
confidence: 97%
“…Little is known about the host protein and lipid requirements of picornaviruses from other genera. Studies with inhibitors of PI4Ks and OSBP suggest that members of the genera Aphthovirus (e.g., equine rhinitis A virus, a close relative of foot-and-mouth disease virus) and Parechovirus do not rely on PI4K/OSBP functions [61,62,78]. Whether these or other picornaviruses co-opt cholesterol/PI4P, either via MCSs or via alternative mechanisms, or have evolved to depend on other machineries to establish their ROs remains to be determined.…”
Section: Hijacking Of Mcs By Other +Rna Virusesmentioning
confidence: 99%
“…OSBP is recruited to ROs through the PI4KB-mediated increase in PI4P and its lipid shuttling activity is essential for viral genome replication. Other OSBP inhibitors (e.g., 25-hydroxycholesterol, AN-12-H5, T-00127-HEV2, TTP-8307, and the natural compound OSW-1) also impaired enterovirus replication [56,[63][64][65]. In a rhinovirus mouse model, prophylactic intranasal treatment with itraconazole reduced viral titers and pathology, raising expectations for topically applied itraconazole to prevent or treat common colds [66].…”
Section: Pi4kbmentioning
confidence: 99%
“…Among the tested compounds, sophocarpinol exerted the most promising activity against not only CVB3 but also CVB1, CVB2, CVB5 and CVB6 with IC 50 ranging from 0.62 to 3.63 mM (SI from 46 to 275), indicating a broad-spectrum anti-CVB activity constituent amentoflavone also exhibit anti-CVB3 activity, both in vitro by preventing cytopathic effect formation in HEp-2 cells and in vivo by reducing mean viral titres in the heart and kidneys as well as mortality of CVB3 infected mice 11 . It was recently reported that, oxysterol-binding protein (OSBP), a PI4P-binding protein that shuttles cholesterol between membrane compartments, is implicated as another host factor for enterovirus replication 12 . OSW-1 (3b,16b,17a-trihydroxycholest-5-en-22-…”
Section: Introductionmentioning
confidence: 99%
“…-O-acetyl-a-arabinopyranoside, a natural compound extracted from the bulbs of the Ornithogalum saundersiae, and itraconazole, a well-known antifungal agent, are inhibitors of viral RNA replication by targeting oxysterol-binding protein (OSBP) and can be potentially used as broad-spectrum inhibitors of enteroviruses 12,13 . In this study, we present the evaluation of antiviral activity of N-substituted derivatives of 1-arylimidazolidyn-2-ylideneurea against the SV-1 14,15 and CVB3.…”
Section: Introductionmentioning
confidence: 99%